Upaya Penanggulangan Pembakaran Lahan Di Kawasan Keselamatan Operasi Penerbangan Oleh Unit ARFF (Airport Rescue And Fire Fighting) PT. Angkasa Pura Indonesia Bandar Udara Internasional Minangkabau - Fitra Oktoriny; Tommy Pratama (Fakultas Hukum Universitas Tamansiswa Padang, 2025)
The prohibition of land burning activities in the flight safety operation area (KKOP) of Minangkabau International Airport (BIM) West Sumatra has been expressly stated in international and national regulations, in international regulations it is regulated in Annex XIV concerning Aerodrome and national regulations prohibition and sanctions are regulated in Law No. 1 of 2009 concerning Aviation. The impact of this land burning has an impact on disrupting flight operational activities and causing material losses for airport managers and airlines as well as inconvenience for airport service users, but until now land burning activities are still ongoing. The formulation of the problem is How are the efforts, obstacles and ways to overcome obstacles in dealing with land burning in the flight safety operation area (KKOP) by the ARFF (Airport Rescue and Fire Fighting) unit of PT Angkasa Pura Indonesia Minangkabau International Airport, West Sumatra?The problem approach used is sociological juridical, meaning that researchers will study the applicable positive rules, then connect them with the reality or implementation that occurs in the field. The nature of this research is descriptive, meaning that it presents data in accordance with the facts in the field systematically and logically. The results of the study on efforts to overcome land burning in the flight safety operation area by the ARFF (Airport Rescue and Fire Fighting) unit of PT Angkasa Pura Indonesia Minangkabau International Airport are with non-penal efforts as follows: Patrol supervision and prevention of fire hazards by the ARFF unit, direct appeal to the community around the airport, socialization and understanding to the community regarding the impact and legal sanctions for land burning activities in the airport KKOP area and carrying out criminal efforts for perpetrators of land burning in the airport KKOP area, The obstacles faced are the social and economic conditions of the community, Lack of public understanding of the impact and legal sanctions for burning land in the BIM airport flight safety operation area (KKOP), Lack of active role from Government Agencies and the absence of criminal law sanctions for perpetrators of land burning around BIM airport. Efforts to overcome these obstacles are Improving the social and economic conditions of the community through the Corporate Social Responsibility (CSR) program, implementing socialization to the community regarding the prohibition and legal sanctions for land burning activities in the BIM airport flight safety operation area (KKOP) on a scheduled basis, and encouraging the application of criminal sanctions for perpetrators of land burning in the BIM flight safety operation area (KKOP).